Analisis Komunikasi Publik Dalam Mewujudkan Kesejahteraan Masyarakat - Mukoyimah, Mukoyimah; Bariyah, Choerul (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2023)
Public communication is one of the efforts to provide information to the public in order to minimize public miscommunication. This study aims to find out how public communication is carried out by the government and investors, in this case, BPI (Bhimasena Power Indonesia) regarding the scope of the PLTU in the Batang region. The scope of PLTU development concerns how the raw materials are used and the safety and welfare of the surrounding community. Research using field research method with a descriptive approach. The main source of information is the results of interviews. While the data analysis technique that the author uses is data reduction then presenting the data and the last is concluding. The results of the author's research show that investors' efforts to socialize the establishment of PLTU are not easy. There are many objections from the community, both fighting for environmental health and land acquisition by the PLTU. The government and investors are trying to educate the public. Coal fuel is not without impact, but this impact can be minimized by having a good living culture and good management of coal waste by BPI. The efforts of the government and BPI in educating the public are carried out using an individual approach (presence at community forums) and also through the media, by providing information, complaints, and education services (in the form of comics). This aims to make it easier for the public to understand the intent and purpose of the establishment of the PLTU.